The Effectiveness of Producing a Blended Learning Environment Based on the Programming of an Educational Robot to Develop Problem-solving Skills in Science for Intermediate School Students in the Kingdom of Saudi Arabia - Elmorsy Agwa, Mohamed Gomaa; El-Desouki, Mohamed Ibrahim; Elnagar, Mohamed Elsayed (European Scientific Journal, ESJ, 2023)
This study aimed to examine the effect of producing a Blended learning environment based on the programming of an educational robot to develop problem-solving skills in Science for intermediate school students in the Kingdom of Saudi Arabia. The sample of the study consists of (60) intermediate school students. A total of Four research questions and hypotheses were used in the study. A pre-post-test design was used to achieve the study's objectives in which special treatment was given to the experimental group, whereas no treatment was given to the control group. SPSS was used as a statistical tool to examine the present research results. The study's results proved the effectiveness of a Blended learning environment based on the programming of an educational robot in developing problem-solving skills in Science for intermediate school students in the Kingdom of Saudi Arabia, as the experimental group showed a better performance in the post-test than the control group. Moreover, the correlation test results indicated a significant positive relationship between the Blended learning environment based on the programming of educational robot performance and students' developing problem-solving skills in Science.